Renal Function, Weaning, and Survival in Patients With Ventilator-Dependent Respiratory Failure. (March 2019) - Datta, Debapriya; Foley, Raymond J.; Wu, Rong; Grady, James; Scalise, Paul
Background: Acute kidney injury in acute critical illness has been associated with poor weaning and survival outcomes. The relation between renal dysfunction as defined by creatinine clearance (CrCl) and weaning from prolonged mechanical ventilation (PMV) is not known. The objective of this study was to determine the relation of measured CrCl to weaning and survival in patients on PMV. Methods: We retrospectively studied 167 patients on PMV admitted to a long-term acute care facility for weaning over a 3-year period. Data obtained included age, gender, admission blood urea nitrogen (BUN), serum creatinine, CrCl, random urine creatinine (RUCr), and 24-hour urinary creatinine (24UCr). Renal dysfunction was defined as normal (CrCl > 90 mL/min), mild (CrCl 60-90 mL/min), moderate (CrCl 30-59 mL/min), and severe (CrCl < 30 mL/min). Primary outcome measured was liberation from PMV, defined as being off ventilator for >7 days. Survival, defined as being alive at discharge, time to wean, and time to discharge alive were secondary outcomes. The association between the studied parameters and outcomes was determined by unpaired t test. The predictive value of studied parameters for weaning and survival was determined by multivariate logistic regression analysis. P < .05 was statistically significant. Results: Mean age was 68.5 (14) years; 49% were males; 64% were liberated and 65.8% survived. Blood urea nitrogen, RUCr, 24Ucr, and CrCl had a significant association with successful weaning. These parameters (except BUN) also had a significant association with survival. A better outcome occurred with CrCl > 90 mL/min. Conclusion: Measured CrCl has a significant relation to successful weaning and survival in patients on PMV and may be useful in prognosticating their outcome.